Leveraging Ottawa Charter strategies to enhance COVID-19 vaccination: A systematic review of global health promotion approaches - Sara Pourrazavi; Behrouz Fathi; Zahra Fathifar; Haidar Nadrian; Hamid Allahverdipour (Health Promotion Perspectives)
Background: Despite global vaccination efforts, many countries struggled to achieve sufficient COVID-19 vaccination coverage. The use of Ottawa Charter health promotion strategies in vaccination programs not only enhances coverage but also fosters sustainable public health outcomes. This systematic review aims to identify actionable strategies to improve vaccination efforts. Methods: This systematic review involved a comprehensive literature search across PubMed, Scopus, Web of Science, and Embase, targeting studies published between January 2020 and August 2024. The search focused on government-led health promotion strategies for enhancing COVID-19 vaccination rates. Strategies were categorized five main areas of the Ottawa Charter for health promotion. Results: A total of 22 health promotion strategies were identified globally, categorized into five key areas based on the Ottawa Charter for health promotion. Notable strategies included engaging community, addressing misinformation, expanding vaccination sites, and providing culturally tailored communication. Conclusion: The findings underscore the significance of utilizing the Ottawa Charter framework to design inclusive and adaptable public health strategies that ensure equitable vaccination coverage globally.